Paeoniflorin inhibits colorectal cancer stem cell properties via regulating LINC01711/KMT2D/KLF7 axis - Wang, Wei; Li, Mei; Hu, Fan; Lin, Renjing; Xu, Chongsi; Xie, Biao (Journal of Gastrointestinal Oncology, 2026)
Background: Paeoniflorin (PF) exerts anti-tumor effects in various cancers. However, the effects of PF on colorectal cancer (CRC) are still unknown. The purpose of this study was to investigate the effects of PF on CRC.Methods: Message RNA (mRNA) levels were analyzed by reverse transcription quantitative polymerase chain reaction. Protein expression was determined by Western blot. Cell migration was determined by transwell assay. Cell viability was determined using cell counting kit-8. Cell proliferation was detected using colony formation and 5-ethynyl-2’deoxyuridine assay. CRC cell stem-like properties were analyzed by sphere formation assay and flow cytometry assay. The interaction between LINC01711 and lysine methyltransferase 2D (KMT2D)/KLF transcription factor 7 (KLF7) was analyzed by RNA pull-down assay. The transcription of LINC01711 was analyzed by luciferase and chromatin immunoprecipitation assays.Results: The results showed that PF inhibited the proliferation, migration, and stem-like behaviors of CRC cells. Moreover, PF inhibited the expression of LINC01711, which formed a turnery structure with KMT2D and KLF7. This turnery structure mediated the activation of KLF7/Wnt/β-catenin signaling. However, PF blocked the interaction between LINC01711 and KMT2D/KLF7, as well as inhibited KLF7-mediated transcription and upregulation of LINC01711. Furthermore, PF inhibited the tumor growth of CRC.Conclusions: Taken together, PF inhibits CRC cell proliferation and stem-like properties via blocking LINC01711/KMT2D/KLF7 axis.